2011
DOI: 10.1073/pnas.1117835108
|View full text |Cite
|
Sign up to set email alerts
|

Lethal mitochondrial cardiomyopathy in a hypomorphic Med30 mouse mutant is ameliorated by ketogenic diet

Abstract: Deficiencies of subunits of the transcriptional regulatory complex Mediator generally result in embryonic lethality, precluding study of its physiological function. Here we describe a missense mutation in Med30 causing progressive cardiomyopathy in homozygous mice that, although viable during lactation, show precipitous lethality 2-3 wk after weaning. Expression profiling reveals pleiotropic changes in transcription of cardiac genes required for oxidative phosphorylation and mitochondrial integrity. Weaning mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(59 citation statements)
references
References 41 publications
3
56
0
Order By: Relevance
“…In two studies using ex vivo perfusion approaches in rat hearts, maintenance on low-carbohydrate diets before ischemia-reperfusion protocols gave conflicting results with regard to infarct size and hemodynamic performance (6,221). Prospective cardioprotective effects of a low-carbohydrate diet may be attributable to an increase in the number of myocardial mitochondria or transcriptional upregulation of key mediators of oxidative phosphorylation (6,112). Cardioprotective effects have been observed using in vivo ischemia-reperfusion approaches in rats subjected to starvation-induced ketosis, initiated through prolonged fasting, and also via intravenous injection of DL-␤OHB immediately before ischemic injury, which conferred a significant decrease in both infarct size and myocardial cell death (191,244).…”
Section: Ketone Bodies and Myocardial Diseasementioning
confidence: 97%
See 1 more Smart Citation
“…In two studies using ex vivo perfusion approaches in rat hearts, maintenance on low-carbohydrate diets before ischemia-reperfusion protocols gave conflicting results with regard to infarct size and hemodynamic performance (6,221). Prospective cardioprotective effects of a low-carbohydrate diet may be attributable to an increase in the number of myocardial mitochondria or transcriptional upregulation of key mediators of oxidative phosphorylation (6,112). Cardioprotective effects have been observed using in vivo ischemia-reperfusion approaches in rats subjected to starvation-induced ketosis, initiated through prolonged fasting, and also via intravenous injection of DL-␤OHB immediately before ischemic injury, which conferred a significant decrease in both infarct size and myocardial cell death (191,244).…”
Section: Ketone Bodies and Myocardial Diseasementioning
confidence: 97%
“…Additionally, limited studies raise the possibility that humans with NAFLD could benefit from low-carbohydrate diet therapy (32,58). An experimental ketogenic diet has been used to mitigate a mitochondrial cardiomyopathy in mice (112). The full scope of cardiovascular diseases responsive to nutritional and/or pharmacological manipulation of ketone body metabolism and the associated metabolic mechanisms remain underexplored.…”
Section: Diagnostic and Therapeutic Targets Of Ketone Body Metabolismmentioning
confidence: 98%
“…As Mediator function is closely associated with energy utilization and homeostasis (22,24,(39)(40)(41), it is not entirely unexpected that overexpression of Cdk8 results in a large enrichment of downregulated mitochondrial-based metabolic genes and pathways (Figures 6 and 7). In fact, we see considerable overlap between the RNA-seq results presented here (885 of 1,160 genes expressed >1.5-fold, r 2 = 0.61) and those from cardiac deletion of the core Mediator subunit Med1 (Med1cKO) that we recently reported (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mice with missense mutations in Med30 develop DCM after weaning. Early lethality in these mice was linked to a decline in mitochondrial function, likely due to decreased expression of genes involved in oxidative phosphorylation in the heart (46). We recently demonstrated that cardiac MED13 regulates metabolic gene expression in the heart.…”
Section: Egr1mentioning
confidence: 99%